Researching Chinese rural-urban relationship within Belgium’s everyday academic life: a reflection on power and intertextuality - Ran Feng (Belgeo)
In this article, by mobilizing the concept of “in-betweenness” and intertextuality, I show how the reflections on my lived experiences of acclimatization and involvement in Belgium has aided in shaping my theoretical understanding of Chongming villagers’ struggles in the eco-island project. Chongming is a rural island in the Yangtse River delta currently integrated in Shanghai’s urban development. My analysis unfolds on two levels. In the first place, my non-Shanghai and non-rural background creates a unique tension with my research topic: the rural reaction to the eco-island urbanization. My position as a migrant in Belgium, navigating the West-East hierarchy, has analogous elements to Chongming elder generation’s relationship to Shanghai, situated in the urban-rural hierarchy. This macro-level resonance has deepened my understanding of local middle-aged and elderly villagers’ general attitude to Shanghai and related self-identity, which significantly influenced their reactions to eco-island projects. On the everyday level, my close ties with village cadres inadvertently limited my access to the ordinary villagers, posing challenges in uncovering the real politics pursued by the villagers. But, like an “ordinary villager” in Chongming I was a part of a marginalized group in the Belgian academic institute. Taking into account the similar collective settings, the struggles I had in Belgium not only informed me, but also increased my sympathy with the unseen side of the village collective. I argue that both Chongming and Belgium served as my field sites that in turn moulded my own subjectivity.